Incomplete immune reconstitution in HIV/AIDS patients on antiretroviral therapy: Challenges of immunological non‐responders - Yang, Xiaodong; Su, Bin; Zhang, Xin; Liu, Yan; Wu, Hao; Zhang, Tong (Journal of leukocyte biology, 2020)
The morbidity and mortality of HIV type‐1 (HIV‐1)‐related diseases were dramatically diminished by the grounds of the introduction of potent antiretroviral therapy, which induces persistent suppression of HIV‐1 replication and gradual recovery of CD4+ T‐cell counts. However, ∼10–40% of HIV‐1‐infected individuals fail to achieve normalization of CD4+ T‐cell counts despite persistent virological suppression. These patients are referred to as “inadequate immunological responders,” “immunodiscordant responders,” or “immunological non‐responders (INRs)” who show severe immunological dysfunction. Indeed, INRs are at an increased risk of clinical progression to AIDS and non‐AIDS events and present higher rates of mortality than HIV‐1‐infected individuals with adequate immune reconstitution. To date, the underlying mechanism of incomplete immune reconstitution in HIV‐1‐infected patients has not been fully elucidated. In light of this limitation, it is of substantial practical significance to deeply understand the mechanism of immune reconstitution and design effective individualized treatment strategies. Therefore, in this review, we aim to highlight the mechanism and risk factors of incomplete immune reconstitution and strategies to intervene. Highlights the mechanism and risk factors of incomplete immune reconstitution and strategies to intervene.